2016
DOI: 10.1111/cea.12722
|View full text |Cite
|
Sign up to set email alerts
|

High‐dose cutaneous exposure to mite allergen induces IgG‐mediated protection against anaphylaxis

Abstract: High-dose cutaneous exposure to dust mites induced effective blocking IgG production, even if accompanied by IgE production. Our data might support the concept that an increase in IgG titre, not a decrease in IgE titre, is a marker of clinical improvement in allergen-specific immunotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 41 publications
1
9
0
Order By: Relevance
“…However, allergen specific IgG competes with allergen specific IgE and thereby protects against allergic immune response, a mechanism that is used during allergen-specific immunotherapy[ 33 ]. Indeed, high-dose HDM exposure can induce IgG-mediated protection against HDM-specific anaphylaxis[ 34 ]. Therefore we hypothesize that in our HDM exposed asthma model elevated HDM specific IgG 1 dampens adaptive immunity.…”
Section: Discussionmentioning
confidence: 99%
“…However, allergen specific IgG competes with allergen specific IgE and thereby protects against allergic immune response, a mechanism that is used during allergen-specific immunotherapy[ 33 ]. Indeed, high-dose HDM exposure can induce IgG-mediated protection against HDM-specific anaphylaxis[ 34 ]. Therefore we hypothesize that in our HDM exposed asthma model elevated HDM specific IgG 1 dampens adaptive immunity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent experimental study using a high-dose cutaneous exposure to Dermatophagoides pteronyssinus mite extract has shown to induce effective blocking IgG production, supporting that the detection of increased IgG antibody titres is a promisor marker of clinical efficacy of AIT [57].…”
Section: Immunotherapy Follow-upmentioning
confidence: 92%
“…50,51 Hirai et al employed a mouse model system whereby mice were cutaneously sensitized to Dermatophagoides pteronyssinus dust mite extract (HDM) to examine the relationship of the dosage of cutaneous allergen exposure, development of IgG-and IgE-specific immune responses, and allergen sensitization. 52 The authors showed that epicutaneous exposure of NC/ Nga mice to various doses of HDM induced a dose-dependent exacerbation of atopic dermatitis (AD)-like skin lesions that was associated with elevated HDM-specific IgG and IgE. Notably, the mice exposed to low doses of HDM demonstrated increased susceptibility to HDM-specific IgE and anaphylaxis, and adoptive transfer of total IgG from HDM-sensitized mice reduced the susceptibility seen in mice exposed to low doses of HDM.…”
Section: Allergen-specific Immunotherapy: the Weight Of Iggmentioning
confidence: 99%